Prayer and Character Building as Core Predictors of Spiritual Growth: Lessons from Christian Higher Education for Global Well-being - Elon, Yunus; Pardosi, Milton Thorman (UIN Sunan Gunung Djati Bandung, 2025)
The world today faces multiple crises—ecological, social, and moral—that call for the emergence of a generation with a strong spiritual foundation, resilience, and clarity of values in every aspect of leadership. This study explored six dimensions of spiritual growth—Abide in Christ, Live by God’s Word, Pray in Faith, Fellowship with Believers, Witness to the World, and Minister to Others—within the context of Christian higher education. Data were collected from 132 students at Universitas Advent Indonesia using the Spiritual Growth Assessment Process (LifeWay Christian Resources). Descriptive analysis revealed that